Identification of a Novel Deep Intronic Variant by Whole Genome Sequencing Combined With RNA Sequencing in a Chinese Patient With Menkes Disease - Zhi, Xiufang; Ai, Qi; Sheng, Wenchao; Yu, Yuping; Shu, Jianbo; Yu, Changshun; Yu, Xiaoli; Li, Dong; Cai, Chunquan (Frontiers in Genetics, 2022)
Background: Menkes disease (MD) is a rare X-linked connective tissue disorder of copper metabolism caused by pathogenic variant(s) in ATP7A gene. The aim of the present study is to determine the clinical characteristics and molecular basis of one patient with MD. Methods: One 10-month-old Chinese boy who met the clinical manifestations of MD was enrolled in this study. Whole genome sequencing (WGS) was performed in the patient in order to identify the variant(s), followed by Sanger sequencing. RNA sequencing (RNA-seq) from whole blood was subsequently applied to assess the effect of variant on transcription levels, and reverse transcriptase-polymerase chain reaction (RT-PCR) was performed for further validation. In addition, X chromosome inactivation (XCI) status of the patient’s mother at the DNA level was measured by capillary electrophoresis. Results: The patient suffered from intermittent convulsions for more than six months, with psychomoto retardation and neurodegenerations. The patient also had curly hair, hypopigmented skin, cutis laxa, decreased muscle strength and hypotonia. MRI showed the intracranial arteries were tortuous with some ‘spiral’ changes. The patient's serum ceruloplasmin level was low. WGS revealed one novel hemizygous variant, c.2627-501C>T (NM_000052.7), located in the deep intronic sequence of ATP7A gene. Sanger sequencing confirmed that the variant was inherited from his mother. RNA-seq confirmed the variant itself, and identified a pseudo-exon inserted between exons 12 and 13 in mRNA of ATP7A. The sequencing results of RT-PCR from the patient confirmed this finding, while neither of his parents detected aberrant splicing. The Capillary electrophoresis results showed that the patient’s mother had a skewed XCI. Conclusion: Our finding of the variant enlarges the variant spectrum in the ATP7A gene. This is a novel deep intronic variant which leads to the activation of a pseudo-exons in the ATP7A gene, and it demonstrates the usefulness of WGS combined with RNA-seq, in terms of revealing disease-causing variants in non-coding regions. Furthermore, the fact that the deep intronic variants cause disease by the activation of pseudo-exon inclusion indicates that in MD this might be an important mechanism.